The Price of Housing in the United States, 1890–2006 - Ronan C Lyons; Allison Shertzer; Rowena Gray; David Agorastos (The Quarterly Journal of Economics, 2026)
Abstract We construct the first annual market rent and home sales price series for American cities over the twentieth century using 2.7 million newspaper real estate listings. Our findings revise several stylized facts about U.S. housing markets. Real market rents did not fall during the postwar period in most cities and rose nationally by 60% from 1890 to 2006. We also document higher sales price growth between 1953 and 1987 relative to previous series. Real prices reached almost four times their 1890 level by 2006. Prices grew most in metros with high demand and low levels of construction. We find that the rent-to-price ratio fell from about 8% in the early twentieth century to 3% by 2006, consistent with declines in the cost of owning housing relative to renting. For the typical year in our period, the annual return to owning housing was 9%, driven mostly by rental returns of 7.7%, with capital gains contributing only 1.3%. While capital gains were close to zero from 1890 to 1940, they grew to nearly a third of total returns from 1970 to 2006.